2018
DOI: 10.1123/jab.2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Movement and Performance Variability: Adaptation of Front Crawl Swimmers to Competitive Swimming Constraints

Abstract: To study the variability in stroking parameters between and within laps and individuals during competitions, we compared and modeled the changes of speed, stroke rate, and stroke length in 32 top-level male and female swimmers over 4 laps (L1-L4) in 200-m freestyle events using video-derived 2-dimensional direct linear transformation. For the whole group, speed was greater in L1, with significant decreases across L2, L3, and L4 (1.80 ± 0.10 vs 1.73 ± 0.08; 1.69 ± 0.09; 1.66 ± 0.09  · s, P < .05). This variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Therefore, based in such differences it should be suggested that these two concepts should not be analysed as one. At least for 200 m races this rational is reinforced by the studies of Simbaña-Escobar et al (2018a) and Simbaña-Escobar et al (2018b). These authors showed that besides an inter-lap variation, an intra-lap variation also occurs.…”
Section: Clean Swim Performancementioning
confidence: 89%
“…Therefore, based in such differences it should be suggested that these two concepts should not be analysed as one. At least for 200 m races this rational is reinforced by the studies of Simbaña-Escobar et al (2018a) and Simbaña-Escobar et al (2018b). These authors showed that besides an inter-lap variation, an intra-lap variation also occurs.…”
Section: Clean Swim Performancementioning
confidence: 89%
“…For the difference between preferred (SR P ) and maximal (SR M ) stroke rates, seven of the sixteen swimmers for whom the regression models between S and SR were significant ( Figure 5) had close SR P and SR M values (difference < 3 cycle/min) (S2F, S2M, S3M, S4M, S5M, S7M, and S9M), whereas the nine others exhibited a difference ≥3 cycle/min between SR P and SR M (S3F, S5F, S7F, S8F, S1M, S6M, S8M, S10M, and S11M) ( Table 2). This difference of 3 cycle/min corresponds to the 5% SR variation regularly observed within and between laps when cycle-to-cycle analyses were performed during 100and 200-m front crawl events in international competition, (see Hellard et al 8 and Simbaña-Escobar et al 10,11 ).…”
Section: Relationships Between Preferred and Maximal Stroke Rate Smentioning
confidence: 91%
“…9 Training swimmers to broaden their range of stroke rates and/or their range of coordination modes is nevertheless not a common concern or strategy for coaches, as they often try to stabilize a given number of strokes or a targeted time that swimmers should maintain through the lap or race. However, various stroke rates and their management have been observed within and between laps during competition 10,11 and between swimmers, 12 suggesting that several profiles of stroke rate management could lead to high swimming performances.…”
mentioning
confidence: 99%
“…Thus, the 200 m event can cater the interest of either sprinters or middle-distance swimmers. In elite swimming, it was shown that swimmers racing in these events presented a low stability, i.e., significant variance between laps (Simbaña-Escobar et al, 2018). Nonetheless, to the best of our knowledge there are no studies on elite junior counterparts racing the 200 m distance, or any other distances.…”
Section: Introductionmentioning
confidence: 96%
“…Literature reports several studies on race analysis of elite swimmers at major competitions (Morais et al, 2020;Simbaña-Escobar et al, 2018). There are studies focused on specific phases of the race such as the start (Burkett et al, 2010;Peterson Silveira et al, 2018), the swim pace (Arellano, Brown, Cappaert & Nelson, 1994;Simbaña-Escobar et al, 2018), turns (Mason et al, 2015;Veiga & Roig, 2016), and finish (Marinho et al, 2020;Suito et al, 2015), or in the combination of some of these phases (Marinho et al, 2020;Morais et al, 2019).…”
Section: Introductionmentioning
confidence: 99%